AMP-chitosan coating with bactericidal activity in the presence of human plasma proteins - Monteiro, C (2020)
Antibiotic resistance is increasing and new strategies are needed to fight infection. Advanced materials are promising tools that can be combined with innovative alternatives to conventional antibiotics to allow more targeted and efficient treatment. In this work, we explored the activity against Staphylococcus epidermidis (S. epidermidis) of the a-helical antimicrobial peptide (AMP) MSI-78(4-20) (KFLKKAKKFGKAFVKIL) when covalently bound to a chitosan coating. The AMP MSI-78(4-20) (17 mer) is an improved version of its parent MSI-78 (22 mer; commercially known as Pexiganan), a cost-effective short AMP, which was demonstrated to be as effective as MSI-78 and less toxic to eukaryotic cells. An MSI-78(4-20)-chitosan coating could be applied in several infection scenarios, ranging from bone implants to wound dressings, as chitosan possesses osteoconductive and hemostatic properties. Cysteine-modified MSI-78(4-20) was covalently immobilized onto the chitosan coating through a succinimidyl-[(N-maleimidopropionamido)-octaethyleneglycol] ester (SM(PEG)8), a heterobifuncional crosslinker, with N-hydroxysuccinimide (NHS) ester and maleimide groups, by its N- and C- termini. The MSI-78(4-20)-chitosan coating demonstrated bactericidal properties independently of the tethering site and an improved performance in the presence of plasma proteins, which mimics conditions that will be encountered in vivo. This AMP-chitosan coating has therefore great potential for applications in medical devices such as implants or even wound dressings.